Modelling of glass fiber reinforced plastic for crash applications - Fang, Jueyi; Gurumurthy, Chirag (My University, 2020)
As every automotive industry is shifting towards lightweight design, composite has become a dominant material due to its high strength to weight ratio. However, a good way of modelling composite materials needs to be investigated to facilitate for the further implementation of composite structures in future designs that are crashable. Several composites demonstrate good energy absorption character during crash e.g. bus roll over, which is bene cial, as this contributes to a steady deceleration of the impacting body. That is what makes it important to use composites for crash applications. It is complex to understand the behaviour of composites under crash condition. Crushing of composite materials is a result of a combination of several failure mechanisms such as matrix cracking, bre debonding, bre fracture etc.. As technology has evolved over the years, it is now possible to mimic these failure mechanisms using commercial FE solvers. A majority of software for reinforced polymers uses various failure techniques and material models, so di erent approaches need to be analysed. This study aims to simulate the mechanical behaviour of glass- bre reinforced composite with the suitable material model available in LS-DYNA and optimise it further to use them in the crash simulation of buses. Virtual simulations were performed with commercial Finite Element (FE) solver LS-DYNA. The mechanical behaviour of two material models (*MAT 058 and *MAT 124 ) for characterising the glass bres have been examined. Virtual simulation test results were compared to a physical coupon test results. After a detailed analysis, calibrated *MAT 058 material model was in good agreement with the experimental data compared to *MAT 124.
Keywords: Finite element method; Chopped strand mat; crash; LS-Dyna; *MAT_058; *MAT_124; Ls-Opt